The effect of teaching the subject of Fibonacci numbers and golden ratio through the history of mathematics - Kaygin, Bülent; Balçin, Bilal; Yildiz, Cemalettin; Arslan, Selahattin (Procedia, social and behavioral sciences, 2011)
This study aims to determine the influence of teaching Fibonacci numbers and golden ratio through history of mathematics on student achievement and the opinions of students regarding this issue. This study was carried out by case study method with 30 students who attended the 8th grade of an elementary school in Erzincan in spring term of 2009-2010 school year. Data were collected with performance test and a questionnaire form composed of 5 open-ended questions. The results showed that teaching Fibonacci numbers and golden ratio which was integrated with the history of mathematics had a positive effect on student achievement.